1994
DOI: 10.1099/13500872-140-9-2271
|View full text |Cite
|
Sign up to set email alerts
|

The 387 kb linear plasmid pPZG101 of Streptomyces rimosus and its interactions with the chromosome

Abstract: The linear plasmid pPZGlOl of Streptomyces rimosus R6 was restriction mapped with the enzymes Asel, Bfrl, Dral and Xbal. It is 387 kb in size and the ends are inverted repeats of a t least 95 kb in length. Twenty spontaneous morphological variants and seventeen auxotrophic mutants were screened for changes in the plasmid. Two strains were found that had lost all plasmid sequences. Four strains had integrated parts of the plasmid into the chromosome. Restriction analysis suggested that at least three of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 18 publications
(5 reference statements)
4
85
0
3
Order By: Relevance
“…Schwan et al, 1995;Montgomery et al, 1996;Zhang et al, 1997). It has also been suggested that some genetic variation in Streptomyces rimosus R6 might be due to replacement of its protein-bound chromosomal telomeres by similar telomeres from the linear plasmid pPZG101 (Gravius et al, 1994). Perhaps terminal exchanges are a common theme among linear replicons in bacteria.…”
Section: Lyme Agent Chromosomal Telomeresmentioning
confidence: 99%
“…Schwan et al, 1995;Montgomery et al, 1996;Zhang et al, 1997). It has also been suggested that some genetic variation in Streptomyces rimosus R6 might be due to replacement of its protein-bound chromosomal telomeres by similar telomeres from the linear plasmid pPZG101 (Gravius et al, 1994). Perhaps terminal exchanges are a common theme among linear replicons in bacteria.…”
Section: Lyme Agent Chromosomal Telomeresmentioning
confidence: 99%
“…Recently, linear plasmids were also found in the genus Mycobacterium (Picardeau & Vincent, 1997 Rhodococcus opacus linear plasmids to be linear as well Gravius et al, 1994;Lezhava et al, 1995;Leblond et al, 1996). The common features of the linear replicons in Streptomyces are perfect or imperfect TIRs, with proteins bound to their ends.…”
Section: Discussionmentioning
confidence: 99%
“…The common features of the linear replicons in Streptomyces are perfect or imperfect TIRs, with proteins bound to their ends. The lengths of TIRs are not uniform: the large linear plasmids SCPl (350 kbp) and pPZGlOl (387 kbp) have very long TIRs of more than 80 kbp (Kinashi et al, 1991;Gravius et al, 1994), and also the linear chromosomes (about 8 Mb) possess TIRs of about 25 kbp (S. liuidans, S. griseus) or even 210 kbp (S. ambofaciens) Lezhava et al, 1995;Leblond et al, 1996). Smaller linear plasmids like pSCLl(11.7 kbp) and pSLA2 (17 kbp) have TIRs of less than 1 kbp (Wu & Roy, 1993;Hirochika et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…60 During the study of genetic instability of S. rimosus R6, one overproducer (MV17) was found to carry a 1-Mb linear plasmid, pPZG103. This plasmid arose from a single crossover between pPZG101 and the chromosome, such that about 200 kb at one end is derived from pPZG101 and the other 800 kb is the chromosomal terminal sequence carrying the oxytetracycline cluster.…”
Section: Pksl In S Lasaliensismentioning
confidence: 99%